Statistical matching using propensity scores: theory and application to the Levy Institute measure of economic well-being - Hyunsub Kum; Thomas Masterson (Levy Economics Institute of Bard College, 2008)
This paper summarizes the background, type, logic, and working procedure of the statistical matching used in the Levy Institute Measure of Economic Well-Being (LIMEW) project to combine the various data sets used to produce the synthetic data set with which the LIMEW is constructed. The authors use the match between the 2001 Survey of Consumer Finances and the Annual Demographic Survey of the Current Population Survey data sets to demonstrate the procedure and results of the matching. Challenges confronted in the use of this technique, such as the distribution of weights, are discussed in the conclusion.
Keywords: C14; C40; D31; 330; Statistical Matching; Survey of Consumer Finances; Annual Demographic Supplement; Distribution of Income and Wealth